2022
DOI: 10.21203/rs.3.rs-2137865/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical Implications of Aberrant PD-1 Expression for Acute Leukemia Prognosis

Abstract: Background: Acute lymphoblastic leukemia (ALL) and acute myeloid leukemia (AML) are the most common types of leukemia in adults with an overall poor prognosis. PD-1 alone or combined with other immune checkpoint blockade is a promising research direction for the treatment of acute leukemia (AL) patients. However, clinical Implications of aberrant PD-1 expression in peripheral CD4+ and CD8+ T lymphocytes of AML and ALL patients in assessing the prognosis of diseases, remains inconclusive. Methods: In the presen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…(P<0.0001) as shown in Figure 2. This result corresponds with Ruan who observed that the expression of PD1 was increased significantly and the levels of PD1 in AML (p<0.0001), and AML (p<0.0001) were obviously higher than those in controls [18]. The high expression of PD-1 the activates of PD-1/PD-L1 signaling pathway continuously and inhibits the various signaling pathways [16] [17].…”
Section: Resultssupporting
confidence: 83%
“…(P<0.0001) as shown in Figure 2. This result corresponds with Ruan who observed that the expression of PD1 was increased significantly and the levels of PD1 in AML (p<0.0001), and AML (p<0.0001) were obviously higher than those in controls [18]. The high expression of PD-1 the activates of PD-1/PD-L1 signaling pathway continuously and inhibits the various signaling pathways [16] [17].…”
Section: Resultssupporting
confidence: 83%